SOVEREIGN GEOGRAPHIES, ERRANT PARTS & EVERYTHING IN ITS PLACE - S. Moy, James (PEOPLE: International Journal of Social Sciences, 2024)
We exist in a significant geo-political nexus in the history of global development. African nations of the Sahel and indigenous peoples around the world have begun to kinetically resist neo-colonial initiatives to reimpose past suppressions. This paper surveys developments from 15th and 16th Century Papal Bulls through, government legislation and policy developments including the American Indian removal act of 1830, Berlin Conference of 1884-85, the Morgenthau Plan, late 20th Century Neo-Colonial exploitation and continuing early 21st century attempts at re-inscription of emergent rentier oppressions and trajectories. Within this context, this piece concludes with a pointed discussion of social media and its place in subverting the governmental attempts to control the narrative of the global order in light of recent geo-political developments and the global history of suppression.